A framework for characterizing RAP clustering in asphalt concrete mixtures. (1st March 2016) - Bressi, Sara; Pittet, M.; Dumont, A.G.; Partl, M.N.
Highlights: Definition of a Clustering Index to quantify the RAP clusters formation. Development of Response Surface Model to describe the RAP clustering phenomenon. RAP clusters formation depends on the sizes and percentages of RAP grains. RAP clusters formation depends on the quality and quantity of the virgin aggregates. Abstract: Recycled Asphalt Pavement (RAP) is commonly used in asphalt for road rehabilitation or new constructions. Nevertheless, some physical and chemical phenomena that occur during production, laying and compaction of mixtures containing RAP are not yet completely explored. One of the main aspects is represented by the interaction between the aged bitumen from RAP and the virgin bitumen added to the mixture as well as the creation of clusters among small-size RAP particles. In this paper several combinations of mixtures are studied, varying the amount of RAP, the type of new binder and the testing temperature in order to obtain a suitable data set for the development of a framework for characterizing clustering of RAP during mixing hot recycled asphalt concrete based on the parameters mentioned above. For analyzing the experiments, the Response Surface Methodology (RSM) was applied. The set of points (combinations tested) for calibration of the models was selected using the Dohelert network, which is a design optimization strategy that allows the effective estimation of the models coefficients. The agglomeration of RAP particles is investigated for all virgin binders used and for all the percentages of RAP. It was shown that the quantity and the quality of virgin aggregates play a significant role in the clusters formation. Moreover, this experimental work suggested that revised formula for the calculation of the bitumen film thickness is needed, in order to include the combined effect of bitumen penetration and fabrication temperature.